The Aerated Compost Extract Increases Growth and Productivity of Red Spinach Plants (Amaranthus tricolor L.) - Siswanti, Dwi Umi (Fakultas Biologi Universitas Gadjah Mada, 2024)
Synthetic fertilizers are widely used in agriculture to increase crop yields. However, the impact can suppress soil microbial life and reduce soil quality. Therefore, a study about fertilizer alternative that does not have an environmental bad impact is necessary, and one of which is a study of compost extract. Compost extract is a liquid extract produced from soaking compost for several days by aeration or non-aeration. The aims of the research are to determine the effect and the best dosage of aerated and non-aerated compost extract on plant growth and productivity. The plant that will be used in this research is red spinach (Amaranthus tricolor L.). This reaserch is conducted in a completely randomized design (CRD) with treatment of compost extract dosage. The chemical parameters of the compost extract analyzed included carbon (C), nitrogen (N), phosphorus (P), and potassium (K) levels. Parameters observed are plant height; number of leaves; fresh and dry weight of roots, stems, and leaves; root shoot ratio; and levels of vitamin C. Data is analyzed using Analysis of variance (Anova), and differences between treatments will test with Duncan Multiple Range Test (DMRT) with a significance level of 95%. The aerated compost extract with an optimum concentration of 75% increased plant height, number of leaves, fresh weight of stems and leaves, and dry weight of stems. The aerated compost extract with 100% optimum concentration increased root fresh weight, root and leaf dry weight, root:shoot ratio, and vitamin C. Keywords: Amaranthus tricolor L.; aerated compost extract; non-aerated compost extract; plant growth; plant productivity.